Decree-Law of the President of the Arab Republic of Egypt No .95 of the Yesr 2015 On Amending Some Provisions of Decree-Law No. 14 of the Year 2012 on the Integrated Development in Sinai Peninsula = قرار رئيس جمهورية مصر العربية بالقانون رقم 95 لسنة 2015 بتعديل بعض أحكام لبمرسوم بقانون رقم 14 لسنة 2012 بشأن التنمية المتكاملة في شبه جزيرة سيناء / presidency - Egypt. presidency (2025)
Decree-Law of the President of the Arab Republic of Egypt No. 95 of the year 2015 On Amending Some Provision of Decree-Law no. 14 of the year 2012 on the integrated development in Sinai Peninsula قرار رئيس جمهورية مصر العربية بالقانون رقم 95 لسنة 2015 بتعديل بعض أحكام لبمرسوم بقانون رقم 14 لسنة 2012 بشأن التنمية المتكاملة في شبه جزيرة سيناء